Dual crosslinked polyamidoxime/alginate sponge for robust and efficient uranium adsorption from aqueous solution. (12th November 2020) - Han, Caina; Yue, Yaru; Xu, Xin; Cai, Dong; Liu, Zhongjie; Chen, Shuaifeng; Luo, Lijie; Xiao, Juanxiu; Wang, Dong
Abstract : A facile, low-cost, organic solvent-free fabrication strategy is developed to prepare a seawater-stable sponge adsorbent from a water-soluble precursor for highly efficient extraction of uranium from seawater and uranium-containing wastewater. Abstract : With proper modification, polyamidoxime (PAO) shows extraordinary solubility in aqueous alkaline solution. A hybrid sponge was prepared by freeze-drying an aqueous solution of PAO/alginate. After simple in situ ionic and covalent crosslinking, the sponge showed highly efficient uranium capture performance with a saturated adsorption capacity of 718.38 ± 12.38 mg g −1, as well as excellent chemical and mechanical stability in running seawater for weeks.